Strength and Durability Properties of Geopolymer Mortar Made with Concrete Waste Powder - Pankaj Saini; Paramveer Singh; Kanish Kapoor (Engineering Proceedings)
With each passing season, the need for sustainability is growing exponentially. This target of sustainability can only be achieved by innovation in new materials and technologies. Geopolymer binders are innovative materials that can replace cement and play a vital role in attaining sustainability in infrastructure. This paper discusses the effective utilization of Concrete Waste Powder (CWP) as a binder to assess the strength and durability properties of geopolymer mortar. Herein a CWP was partially replaced with Ground Granulated Blast Furnace Slag (GGBS) at different replacement levels of 0%, 10%, and 20%. The alkaline solution for geopolymer mortar was made from sodium hydroxide and sodium silicate solutions. For all geopolymer mortar mixes, 0.45 alkali/binder ratio, 12 molarity (M) of sodium hydroxide, 2 of sodium silicate/sodium hydroxide ratio, and 0.35 of water/solid were kept constant. The strength property in terms of compressive strength and durability was accessed in terms of water absorption and porosity of all geopolymer mortar mixes at both ambient and heat curing conditions at 7 and 28 days. The presence of silica, alumina, and calcium in CWP makes it a potential binder for geopolymer mortar. The results suggest that increasing the substitution of GGBS with CWP improves the strength and durability of geopolymer mortar mixes by providing appropriate calcium content along with a geopolymer reaction. The compressive strength increases and water absorption and porosity decrease significantly with a 20% content of GGBS. The utilization of CWP in the production of geopolymer mortar sourced from concrete waste can help to achieve a sustainable environment.